the Description Of Management Leadership, Supervision In Improving The Performance Of Tutors At PKBM Lembah Mentenang - Fithriazni (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study explores the leadership of managers and supervision in improving tutor performance at the Lembah Mentenang Community Learning Center (PKBM). Non-Formal Education (PLS) has an important role in developing skills, attitudes, and values ​​that are relevant to the needs of individuals and society. PKBM as a form of non-formal education plays a vital role in providing community-based education services. However, the results of the study indicate that there are problems in tutor services at PKBM Lembah Mentenang, which affect the performance and quality of education services. Through an analysis of the roles of leadership and supervision, this study highlights the importance of effective management and training for tutors to improve the quality of learning. The findings of the study provide strategic recommendations for improving tutor performance through ongoing supervision and capacity development of PKBM managers.